Cultural and medical occupatition and crafts in the Khorasan region during the era states of the East until the coming of the Mongols (820-1220 AH / 205-617 AD) - Chalabi , Rondik; Tawfiq, Zrar (Humanities Journal of University of Zakho, 2021)
This study deals with the cultural and medical occupatition and crafts in the khorasan region until the coming of the Mongols, and it examins and how they developed in that era by presenting the information mentioned in the sources. The research consists of an introduction and two chapters, the introduction is devoted to shed light on the title of the research, so we defined the terms profession and craft and then the designation and its quarters and the countries that ruler it. The first chapter focused on cultural professions and crafts such as calligrapher,papers,copyist, and painter, while the second chapter dealt with medical professions and crarfts such asphamacis ,perfumer ,kohl, circumcision,hamame,washing. The stude concluded with presenting the most important findings that it reached, and the most important of wich isthat the cities of the khorasan region witnessed a great development of cultural and medical professions and crafts, which led to highlighting the personality of the Khorasan civilized society, it turned out that most of them were scholars and classified books, in addition to that most of them practiced that work in order to earn a living.